UNVEILING THE DYNAMICS: EXPLORING CHALLENGES IN ENGLISH LANGUAGE TEACHING ACROSS VARIED CLASSROOM SIZES IN ACEH, INDONESIA - Rizka Marlisa Aini; Mulyadi Syahputra (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research delves into the nuanced landscape of English Language Teaching (ELT) in Aceh, Indonesia, focusing on the distinctive challenges faced by educators in classrooms characterized by divergent sizes—ranging from larger classes with approximately 35 students to smaller, more intimate settings accommodating around 5 students. The study aims to uncover the multifaceted difficulties encountered by teachers in each context, exploring the impact of class size on instructional methods, student-teacher interactions, and overall learning outcomes. Through a combination of qualitative interviews, classroom observations, and teacher surveys, the research seeks to identify common obstacles as well as unique issues associated with both large and small class environments. By gaining insights into these challenges, the study aspires to inform targeted strategies and recommendations for enhancing the quality of English language education in Aceh, fostering more effective teaching practices and improving the educational experience for both teachers and students in diverse classroom settings.